Model Manajemen Ekstrakurikuler Dalam Membentuk Karakter Religius Siswa Di Kecamatan Praya Tengah - Eli Ernawati; Yakin, Nurul; M. Harja Efendi (LPPM IAIN Sorong, 2024)
This study explores the extracurricular management models in schools within Praya Tengah Subdistrict, focusing on religious character development. Employing a qualitative research approach, data was collected through observation, interviews, documentation, and questionnaires. Madrasah Aliyah Darul Anshor and Madrasah Aliyah Nurussabah utilize the P-I-E model (Planning, Implementation, Evaluation), while SMK Negeri 2 Praya Tengah employs the POAC model (Planning, Organizing, Actuating, Controlling) for extracurricular activities. Religious character traits identified include faith, devotion, good manners, cleanliness, sincerity, discipline, love for the country, leadership, and a spirit of helpfulness. The implementation of extracurricular models in shaping religious character involves detailed planning, foundation supervision, and end-of-lesson evaluations based on student behavior. SMK Negeri 2 Praya Tengah's approach includes planning with clear indicators, organizing through task division, emphasizing spiritual immersion in implementation, and organizational evaluation to monitor extracurricular activities and assess student attitudes and behavior annually.